“evaluación estructural de las uniones soldadas en la construcción de calderas, como medida de asegurar su resistencia mecánica” - Quispe Infantes, Joel Rolando (2016)
The purpose of this study was to perform a procedure for structural evaluation of the welds in the construction of furnaces, such as to ensure its mechanical strength. For the testing of the hypothesis of work I use a 50 BHP firetube boiler currently in use for determining the loss of material (thickness) in the structural parts, himself the strength assessment (hydrostatic test) was performed in a standard of 3BHP tubular shell boiler. We evaluated the mechanical strength; primarily evaluating the tensile strength of the material after making the weld, its yield strength which determines the allowable tension coefficient in the present study was determined at 80 MPa (12019 psi); the weld has a tensile strength of 177.5 MPa (26,619 psi) Analytically determined a longitudinal stress of 5 926,10 Psi and Psi hoop stress 13025.3; for a type boiler pirotubular 50bhp with plate thickness 3.8 "; 1500 mm in diameter. To design features a 50bhp Caldra of design pressure 150psi; hull deformation 0.6687 inch was determined and the deformation of the caps was determined in -0.0295 inch. Keywords: boilers, structural evaluation, welded seams